2008
DOI: 10.1039/b812797b
|View full text |Cite
|
Sign up to set email alerts
|

Redox bifunctionality in a Pt(ii) dithiolene complex of a tetrathiafulvalene diphosphine ligand

Abstract: The Pt(ii) dithiolene complex of a tetrathiafulvalene diphosphine ligand exhibits two reversible redox systems at close potentials, localized on the weakly interacting TTF (tetrathiafulvalene) and Pt(dmit) moieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…). Noh et al managed to abstract the chlorides by a reaction with [Bu 2 Sn(dmit)] (dmit = 4,5-dimercapto-1,3-dithiole-2-thione), which afforded a mixed TTF-diphosphine-dithiolene complex, [(dm-TTFdpp 2 )Pt(dmit)] 83. DFT calculations performed on this molecule showed that the HOMO resides on the Pt(dmit) moiety, while the HOMO-1 is located on the TTF unit.…”
mentioning
confidence: 99%
“…). Noh et al managed to abstract the chlorides by a reaction with [Bu 2 Sn(dmit)] (dmit = 4,5-dimercapto-1,3-dithiole-2-thione), which afforded a mixed TTF-diphosphine-dithiolene complex, [(dm-TTFdpp 2 )Pt(dmit)] 83. DFT calculations performed on this molecule showed that the HOMO resides on the Pt(dmit) moiety, while the HOMO-1 is located on the TTF unit.…”
mentioning
confidence: 99%
“…The cyclic voltammogram of (dfppe)Pt(dmit) exhibits a reversible cycle at / = 0.871 V ( = 0.921 V and = 0.820 V), and an irreversible anodic peak at = 1.600 V (Figure 2). This half-wave potential can be attributed to the redox process of the Pt(dmit) moiety [23], which suggests that [(dfppe)Pt(dmit)] + , formed during the first redox process at / = 0.871 V, is well stabilized by the Pt(dmit) moiety. This potential is higher than that of (dppe)Pt(dmit) ( / = 0.777 V), indicating that the F-ended functional groups of (dfppe)Pt(dmit) decreased the donor capability of the Pt(dmit) moiety compared to H-ended functional groups of (dppe)Pt(dmit).…”
Section: Electrochemical Analysismentioning
confidence: 92%
“…In the case of the (dfppe)Pt(dmit) chemosensor, however, only the Hg 2+ ion led to the evolution of a new absorption peak at 523 nm with a decrease in intensity at λ 2 . This bathochromic shift was accompanied by a color change of the solution to vivid red, as seen in Figure 3. 3,4-dimethyl-3',4'-bis(diphenylphosphino)tetrathiafulvalene), indicating that they originated from the absorption of the >C=S moiety [23]. As various metal cations were added to the yellow solution of (dppe)Pt(dmit), the absorption intensity at λ1 decreased, with concurrent evolution of new peaks for the three metal ions (Hg 2+ , Cu 2+ , and Ag + ) in the higher wavelength region: the characteristic bathochromic shift to 558 nm for Hg 2+ , a shift to 700-800 nm for Cu 2+ , and a slight increase (and consequently, a weak color change in Figure 3A) at approximately 530 nm for Ag + .…”
Section: Absorption Spectroscopy On Sensing Of Metal Ionsmentioning
confidence: 99%
“…The thiolate (P2)Pt(SAr) 2 complexes where SAr is benzenethiolate (BT), or 3,5-dimethylbenzenethiolate (DMBT), were prepared as previously described for dithiolene complexes [10,11], by the metathesis reaction of (P2)PtCl 2 [9g] with the corresponding arylthiols (ArSH) in the presence of NEt 3 (Scheme 4). Purification by column chromatography afforded the products in 60% yield.…”
Section: Synthesesmentioning
confidence: 99%
“…Similarly, in tetrathiafulvalenyl-based (P2)Pt(dithiolene) complexes such as (P2)Pt(dmit) or (P2)Pt(dddt) (Scheme 3) [10,11], up to four oxidation waves were identified, which were attributed to the sequential oxidation of the independent redox moieties, namely the TTF core on the one hand and the Pt(dddt) moiety on the other hand.…”
Section: Introductionmentioning
confidence: 98%